Awareness and acceptance of cervical cancer screening among women attending a tertiary care hospital: a cross-sectional study - Sanavelli, Ramajyothi; Rao, C. V. Lakshmi; Kothapally, Kavitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Cervical cancer remains a major public health challenge in India despite the availability of effective screening methods and HPV vaccination. Limited awareness and poor utilization of screening services contribute significantly to delayed diagnosis. Methods: A hospital-based cross-sectional study was conducted among 334 married women aged 20–65 years attending the gynaecology outpatient department of a tertiary care hospital in Telangana from February-November 2025. Data were collected using a pretested structured questionnaire. Statistical analysis was performed using SPSS version 26. Chi-square test and multivariate logistic regression were applied. A p value <0.05 was considered statistically significant. Results: Only one third (31.4%) of participants were aware of cervical cancer. Awareness regarding symptoms (13.5%), risk factors (8.9%), preventive measures (6.9%), and HPV vaccination (14.0%) was low. Awareness of screening tests was reported by 12.8%, and only 7.0% had ever undergone screening. Despite poor knowledge and minimal screening practice, willingness to undergo screening was high (82.0%). On multivariate analysis, employment status (Adjusted OR 2.31; 95% CI: 1.18-4.52), knowledge of screening tests (Adjusted OR 3.11; 95% CI: 1.49-6.48), and willingness to undergo screening (Adjusted OR 5.62; 95% CI: 2.71-11.64) were independent predictors of awareness. Conclusions: Awareness and utilization of cervical cancer screening services were inadequate despite high willingness. Strengthening targeted health education and provider-initiated counseling is essential to improve screening uptake.